Olfactory Dysfunction in COVID‐19 Patients: Prevalence and Prognosis for Recovering Sense of Smell. (14th July 2020) - D'Ascanio, Luca; Pandolfini, Manlio; Cingolani, Cristina; Latini, Gino; Gradoni, Paolo; Capalbo, Maria; Frausini, Gabriele; Maranzano, Massimo; Brenner, Michael J.; Di Stadio, Arianna
Abstract : While olfactory dysfunction associated with coronavirus disease 2019 (COVID‐19) has attracted considerable interest, few studies have tracked outcomes at serial time points or beyond 2 weeks. Furthermore, data are conflicting regarding whether COVID‐19 severity correlates with degree of olfactory dysfunction. This prospective case‐control study analyzed prevalence and severity of subjective loss of smell in outpatients (n = 23) and inpatients (n = 20) with confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection vs healthy controls (n = 25). Olfactory dysfunction was reported more commonly in COVID‐19 patients than in healthy controls ( P <. 001), and outpatients paradoxically reported loss of smell more commonly than inpatients ( P =. 02). Headaches were present in 52% of patients with olfactory dysfunction. Anosmia or hyposmia persisted beyond 5 days but most of the patients recovered by 30 days, suggesting favorable prognosis for olfaction. Differences between inpatients and outpatients are potentially reflective of timeline of olfactory symptoms and contextual factors, underscoring the importance of corroborative objective testing, coupled with careful tracking of temporal relationships.